2021
DOI: 10.1186/s10020-021-00416-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin alleviates the calcification of aortic valve interstitial cells through activating the PI3K/AKT pathway in an AMPK dependent way

Abstract: Background Calcific aortic valve disease (CAVD) is the most prevalent valvular disease worldwide. However, no effective treatment could delay or prevent the progression of the disease due to the poor understanding of its pathological mechanism. Many studies showed that metformin exerted beneficial effects on multiple cardiovascular diseases by mediating multiple proteins such as AMPK, NF-κB, and AKT. This study aims to verify whether metformin can inhibit aortic calcification through the PI3K/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The function and pathway enrichment showed ECM receptor interaction signaling pathways were significantly enriched in our analysis. Compared to other microarray datasets, enrichment analysis found PI3K/AKT signaling pathway in an AMPK-dependent manner was inhibited in CAVD [30], our enrichment results also revealed that the downregulated DEmRNAs could enriched in AMPK signaling pathway. Among the DEmRNAs involved in the lncRNA-miRNA-mRNA ceRNA network, COL4A1, COL4A2, COL4A3, COL1A1, COL6A3 and COL9A1 were belong to constitute of type I, IV, VI and IX collagen, which are structural proteins in the ECM.…”
Section: Discussionmentioning
confidence: 58%
“…The function and pathway enrichment showed ECM receptor interaction signaling pathways were significantly enriched in our analysis. Compared to other microarray datasets, enrichment analysis found PI3K/AKT signaling pathway in an AMPK-dependent manner was inhibited in CAVD [30], our enrichment results also revealed that the downregulated DEmRNAs could enriched in AMPK signaling pathway. Among the DEmRNAs involved in the lncRNA-miRNA-mRNA ceRNA network, COL4A1, COL4A2, COL4A3, COL1A1, COL6A3 and COL9A1 were belong to constitute of type I, IV, VI and IX collagen, which are structural proteins in the ECM.…”
Section: Discussionmentioning
confidence: 58%
“…The PI3K-AKT signaling pathway has been implicated in CAVD. En et al [47,48] found that DEGs between normal aortic valves and calcific aortic valves were mainly enriched in the PI3K-AKT signaling pathway. Moreover, they observed a decrease in the expression of P-AKT and the ratio of P-AKT to AKT in calcific aortic valves.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-101-3p regulates the PTEN/AKT axis in trophoblast cells in the placenta (Zhang et al 2022 ). Metformin can inhibit AVICs calcification in vitro by activating the PI3K/AKT signaling pathway (En et al 2021 ). Yang et al ( 2022 ) found that LEVs might inhibit neuron apoptosis via the miR-101a-3p/c-Fos/TGF-β axis, and has-miR-101-3p is a potential marker of neurological recovery in IS patients.…”
Section: Discussionmentioning
confidence: 99%